Radio access point design for radio over fiber technology - Mohammoud Hadow, Mohammoud Munsor (2008)
Wireless local area network (WLAN) is being used at increasing number of places. In office buildings, hospitals, airport lounges, etc. with the raise in demand for higher speed data delivery, these WLAN need to provide higher data transfer capacities, which requires high microwave frequencies. Thus, the reach of the radio antenna station gets smaller and ever more radio access point (RAP) is needed to cover a certain area. To keep station’s cost under control, the antenna stations should be as simple as possible and as much as possible signal processing signal functions should be centralized at the head end station. The modulated microwave signals need then to be carried transparently between the radio access point (RAP) and head end station. Single mode optical fiber, as extensively used in long distance 50 km and metropolitan network, offer adequate bandwidth for this. The purpose of this study is to design and simulate a radio access point for radio over fiber technology. The simulations were performed using Optisytem. The main components were electroabsoaption modulator (EAM) as radio access point instead of the component Power Amplifier (PA) and Band-pass Filter (BPF). The radio access point is simulated at frequency of 2.4 GHz.